Pengaruh kesadaran metakognisi terhadap kemampuan berpikir kritis mahasiswa PGSD UNS Surakarta - Shintawati, Aisyah; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Didaktika Dwija Indria, 2023)
Critical thinking is an important ability for students to face the demands of the times. One of the factors of a person's critical thinking is the existence of metacognition awareness in a person. Metacognitive awareness is able to train one's way of thinking in controlling the process of cognition by involving critical thinking in that process. This research was conducted to investigate the effect of metacognition awareness on the critical thinking skills of PGSD UNS students for the 2022/2023 academic year. This study uses a quantitative approach to the type of associative research. The population in this study were all second semester students using Cluster Random Sampling as a sampling technique. Data analysis techniques in this study used descriptive statistical analysis and inferential statistics including prerequisite analysis tests and hypothesis testing. The results of the study based on the significance test of the regression coefficient (T test) obtained t count > t table (2.049 > 1.982) and Sig. 0.042 <0.05. The coefficient of multiple linear regression is positive by 0.384 which means that there is a unidirectional relationship which means that there is a unidirectional relationship, then increased metacognition awareness will be followed by increasing critical thinking skills, while the result of the determination coefficient is 20%. These results indicate that metacognition awareness affects the critical thinking skills of PGSD UNS Surakarta students for the 2022/2023 academic year.